STUDENTS' PERCEPTIONS ON TIKTOK APPLICATION FOR LEARNING ENGLISH - Tri Nauli Efivania; Urai Salam; Eka Fajar Rahmani (JEELL (Journal of English Education, Linguistics and Literature), 2025)
This research aimed, to describe the students’ perception on TikTok application for learning English to the eleventh-grade students in SMA Negeri 1 Mempawah Hulu. The method used in this research is a descriptive study. The questionnaire was conducted on the eleventh-grade SMA Negeri 1 Mempawah Hulu. There were 83 students who fulfilled the questionnaires. The findings showed that most students had positive perceptions of using the TikTok application to learn English. Students perceive TikTok as a tool for improving English skills, finding it enjoyable and confidence-boosting. The platform gave convenience, ease of use and access, and abundant English content.